Performance analysis of physical layer security based on channel correlation - Xuanli WU; Zhicong XU; Yuchen WANG; Yong LI (Tongxin xuebao)
In view of the correlation of the main and eavesdropper’s channels in physical layer security, the impact of channel correlation on the secrecy performance was studied, the exact form ulations of ergodic secrecy capacity and secrecy outage probability were derived, and then the asymptotic formulations in the scenarios where the channel states were large and small were given.The theoretical analysis were verified by the numerical simulations.The simulation results show that channel correlation will cause the loss of ergodic secrecy capacity, however, it does not mean the outage probability of communication will increase with high channel correlation.Actually, when the outage rate is set reasonably, the impact of channel correlation is related to the average signal-to-noise ratio (SNR) at the receiver end.At high SNR range, high correlation will decrease the outage probability, at low SNR range, high correlation will increase the outage probability, and at medium SNR range, the correlation will not affect the outage probability significantly.Based on the above conclusion, the parameters can be set according to SNR and correlation, so that the secrecy performance can be maintained.